FIGURE 53. A–C, E, F in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean ... - In, First Published (Zenodo, 2022)
FIGURE 53. A–C, E, F, Plagusia depressa (Fabricius, 1775). A, B, Male, cl 33 mm, cw 37 mm (MZUSP 41244). C, Male, cl ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on page 103, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...